Student Performance as Social Worker inside Child Care Services Practice at Vocational Social Work Department - Yosi Agustina; Yoyoh Jubaedah; Nenden Rani Rinekasari (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2025)
The research entitled "Students' Performance as Social Worker in the Practice of Child Support Services at Vocational Schools, Department of Social Work" aims to determine the performance of students as a social worker in the practice of child support services as well as to obtain data on student performance as a social worker in the practice of mentoring services which include cognitive, psychomotor and affective aspects. This research applies a descriptive method with a quantitative approach, using data collection techniques through interview techniques, observation, and the distribution of performance assessment tools. The population in this study consisted of one productive teacher majoring in Social Work who taught Child Care and Advocacy subjects in class XI Social Work 3, totalling 35 people. The results of this research show that students have a social worker role as companion, facilitator, and educator in accompanying, facilitating, and teaching child clients about fine motor skills, gross motor skills, and child socialization. This analysis focuses on three aspects of assessment, namely cognitive, psychomotor and affective assessment.